A Major Role for the Plastid-Encoded RNA Polymerase Complex in the Expression of Plastid Transfer RNAs. Issue 1 (18th November 2013) - Williams-Carrier, Rosalind; Zoschke, Reimo; Belcher, Susan; Pfalz, Jeannette; Barkan, Alice
Abstract : Proteins that associate with the plastid-encoded RNA polymerase are required for robust expression of numerous plastid tRNAs . Abstract: Chloroplast transcription in land plants relies on collaboration between a plastid-encoded RNA polymerase (PEP ) of cyanobacterial ancestry and a nucleus-encoded RNA polymerase of phage ancestry. PEP associates with additional proteins that are unrelated to bacterial transcription factors, many of which have been shown to be important for PEP activity in Arabidopsis ( Arabidopsis thaliana ). However, the biochemical roles of these PEP -associated proteins are not known. We describe phenotypes conditioned by transposon insertions in genes encoding the maize ( Zea mays ) orthologs of five such proteins: ZmPTAC2, ZmMurE, ZmPTAC10, ZmPTAC12, and ZmPRIN2. These mutants have similar ivory/virescent pigmentation and similar reductions in plastid ribosomes and photosynthetic complexes. RNA gel-blot and microarray hybridizations revealed numerous changes in plastid transcript populations, many of which resemble those reported for the orthologous mutants in Arabidopsis. However, unanticipated reductions in the abundance of numerous transfer RNAs (tRNAs) dominated the microarray data and were validated on RNA gel blots. The magnitude of the deficiencies for several tRNAs was similar to that of the most severely affected messenger RNAs, with the loss of trnL-UAA being particularly severe. These findings suggest that PEP and its associated proteins are critical for the robust transcription of numerous plastid tRNAs and that this function is essential for the prodigious translation of plastid-encoded proteins that is required during the installation of the photosynthetic apparatus.